2005
DOI: 10.1111/j.1600-9657.2004.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Apexification: a review

Abstract: This paper reviews the rationale and techniques for treatment of the non-vital immature tooth. The importance of careful case assessment and accurate pulpal diagnosis in the treatment of immature teeth with pulpal injury cannot be overemphasized. The treatment of choice for necrotic teeth is apexification, which is induction of apical closure to produce more favorable conditions for conventional root canal filling. The most commonly advocated medicament is calcium hydroxide, although recently considerable inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
411
0
38

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 474 publications
(474 citation statements)
references
References 95 publications
0
411
0
38
Order By: Relevance
“…Considering these aspects, a more predictable treatment (apexification) was the Intracanal dressing paste composed by calcium hydroxide, chlorhexidine and zinc oxide for the treatment of immature and mature traumatized teeth treatment of choice in the present study. Apexification usually involves refreshing the calcium hydroxide paste every three months, requiring multiple visits with heavy demands on patients and operators, inevitable clinical costs, and the increased risk of tooth fracture, since the use of calcium hydroxide requires many dressing changes until a calcified barrier isformed 12,22 . This study demonstrated an alternative to periodic changes of intracanal medication in apexification, using a paste composed by calcium hydroxide, chlorhexidine and zinc oxide.…”
Section: Discussionmentioning
confidence: 99%
“…Considering these aspects, a more predictable treatment (apexification) was the Intracanal dressing paste composed by calcium hydroxide, chlorhexidine and zinc oxide for the treatment of immature and mature traumatized teeth treatment of choice in the present study. Apexification usually involves refreshing the calcium hydroxide paste every three months, requiring multiple visits with heavy demands on patients and operators, inevitable clinical costs, and the increased risk of tooth fracture, since the use of calcium hydroxide requires many dressing changes until a calcified barrier isformed 12,22 . This study demonstrated an alternative to periodic changes of intracanal medication in apexification, using a paste composed by calcium hydroxide, chlorhexidine and zinc oxide.…”
Section: Discussionmentioning
confidence: 99%
“…Although earlier studies recommended the use of a Ca(OH)2 prior to MTA placement, recent studies report that the initial use of Ca(OH)2 paste was not necessary for apexification to occur, and it has shown to be strongly related to the extrusion of MTA and formation of barriers beyond the limits of the root canal walls. 3 The major problem in cases of a wide open apex is the need to limit the material to the perforation, thus avoiding the extrusion of a large amount of material into the periodontal tissue [18,19]. A large volume of the extruded material may set before it disintegrates and get resorbed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently MTA has also been emerged strongly as artificial rootend closure material in open apices. Both materials were found to stimulate the formation of mineralized tissue, thereby providing an adequate seal in the apical region [17] MTA, a bio-compatible material, can be used to create a physical barrier that also helps in formation of bone and periodontium around its interface [1][2][3][4][5]. Although earlier studies recommended the use of a Ca(OH)2 prior to MTA placement, recent studies report that the initial use of Ca(OH)2 paste was not necessary for apexification to occur, and it has shown to be strongly related to the extrusion of MTA and formation of barriers beyond the limits of the root canal walls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 There was a requirement for multiple visits and a lengthy time period (average 12 months) before a root filling could be completed. 12 More recently, an alternative 'apexification' protocol involved placement of mineral trioxide aggregate (MTA) which acts as an artificial barrier on which a hard tissue barrier forms. 13 An advantage of this technique is it is generally completed in one or two 446 ª 2010 Australian Dental Association…”
Section: Introductionmentioning
confidence: 99%